Chitinase-3-like 1 regulates TH2 cells, TFH cells and IgE responses to helminth infection - Curtiss, Miranda L.; Rosenberg, Alexander F.; Scharer, Christopher D.; Mousseau, Betty; Benavides, Natalia A. Ballesteros; Bradley, John E.; León, Beatriz; Steele, Chad; Randall, Troy D.; Lund, Frances E. (Frontiers in Immunology, 2023)
Data from patient cohorts and mouse models of atopic dermatitis, food allergy and asthma strongly support a role for chitinase-3-like-1 protein (CHI3L1) in allergic disease. To address whether Chi3l1 also contributes to TH2 responses following nematode infection, we infected Chi3l1-/- mice with Heligmosomoides polygyrus (Hp) and analyzed T cell responses. As anticipated, we observed impaired TH2 responses in Hp-infected Chi3l1-/- mice. However, we also found that T cell intrinsic expression of Chi3l1 was required for ICOS upregulation following activation of naïve CD4 T cells and was necessary for the development of the IL-4+ TFH subset, which supports germinal center B cell reactions and IgE responses. We also observed roles for Chi3l1 in TFH, germinal center B cell, and IgE responses to alum-adjuvanted vaccination. While Chi3l1 was critical for IgE humoral responses it was not required for vaccine or infection-induced IgG1 responses. These results suggest that Chi3l1 modulates IgE responses, which are known to be highly dependent on IL-4-producing TFH cells.